Brazil: an economy caught in a financial trap (1993-2003) - Bibiana Medialdea (Brazilian Journal of Political Economy, 2013)
In the early 1990s, Brazil entered a financialized economic dynamic in which short-term financial valorization generated by the issuing of guaranteed public debt overshadowed the entire economy. This article analyzes Brazilian economic processes between 1993 and 2003, in particular the bi-directional relationship with external vulnerability, erratic international financing behavior and how State actions to obtain and maintain these resources fostered financialization. As a result, the entire economy became enmeshed in a self-perpetuating trap in which financial activity was predominant over economic activity.